Efficacy of stem cells in maxillary sinus floor augmentation: systematic review and meta-analysis - Niño-Sandoval, T. C.; Vasconcelos, B. C.; D. Moraes, S. L.; A. Lemos, C. A. [UNESP]; Pellizzer, E. P. [UNESP] (Elsevier, 2018)
The aim of this review was to test the hypothesis of no difference in the efficacy of bone regeneration when using stem cells in maxillary sinus floor augmentation surgery in comparison to other grafts. Nine randomized clinical trials and one follow-up study involving human subjects were identified through a search of the PubMed/MEDLINE, Scopus, Cochrane, and Web of Science databases, supplemented by a hand search. No significant difference between groups was found for the implant survival rate, increase in bone height, marginal bone loss following implant placement, or new bone formation. With regard to the residual bone graft, an effect favouring the graft group at 3–4 months (P = 0.001) and favouring the stem cell group at 6 months (P = 0.01) was found. Analyses of the subgroup in which the BMAC system extraction method was used in combination with Bio-Oss, revealed no difference in new bone formation; however, the results for residual bone graft at 3 months favoured the control graft (Bio-Oss) (P = 0.01), but at 6 months favoured the stem cells (Bio-Oss + BMAC system) (P = 0.01). Based on all findings, the use of stem cells does not contribute significantly to greater implant survival rates or the efficacy of bone regeneration following sinus lift procedures.
Keywords: review; sinus augmentation; sinus lift; stem cells